Ultrastructural Aspects of the Prenatal Bovine Ovary Differentiation with a Special Focus on the Interstitial Cells. (21st July 2016) - Kenngott, R. A.‐M.; Scholz, W.; Sinowatz, F.
Summary: The aim of this investigation was to study the ultrastructural features during the development of fetal bovine ovaries (crown rump length ranging from 11.4 to 94.0 cm). An interesting observation was the occurrence of big elongated cells containing a variety of electron dense granules and light homogenous vacuoles/bodies. They were located between the stroma cells surrounding the germ cell cord ends, adjacent to the first formed primordial follicles, typically situated near blood vessels. ER alpha and ER beta receptor positive cells could be detected in the same regions by means of immunohistochemistry. Intercellular bridges linked the germ cells nests oogonia. Germ cell cords consisted of centrally located, large, pale oogonia, surrounded by elongated somatic cells with very long cytoplasm extensions. Primordial follicles with flat pale follicular cells could be observed on the inner end of the cords. Extrusions of the outer nuclear membrane could often been recognised in voluminous oocytes.